Role of brain image in neurological complications of eclampsia (Bangladesh Medical Journal Khulna, 2025)
Background: Eclampsia is frequently associated with unexplained coma and takes prolong time in clinical recovery. Neuroimaging of head may be helpful to detect abnormal neurological findings and proper care in Eclampsia. Objective: The objective of the study was to investigate cerebral complications of Eclampsia. For this we corelate neuroimaging study in a series of eclampsia population presented with neurological symptoms. Methods: This one year prospective observational study of Eclampsia was conducted in the Obs and Gyne department of Khulna medical college hospital . Available clinical data were extracted from obstetric records. Computed Tomography (CT) findings of head were studied with respect to neurological signs and symptoms. Results: A total of 92 women with Eclampsia, age group between 16-37 years were studied. 48 (52.7%) of mothers had severe hypertension and proteinuria in 67 (72%) cases. CT scan were abnormal in 21 (70%) cases. Hypertensive encephalopathy were mostly associated with PRES (posterior reversible encephalopathy syndrome) in CT among 20 (66.66%) patients. Prolonged coma, HDU care were more in those with positive CT scan, but not statistically significant. Pearson coefficient was significant in correlation of Intrauterine foetal death and maternal severe hypertension. Conclusion: Cerebral odema and PRES are frequent neuroimaging pathology with Eclampsia,but proper detection is a challenge in resource poor settings. Altered level of consciousness should be a warning for possible brain lesions. Early CT scan of Brain can provide useful information and prompt supportive care preventing death from brain damage.Bang Med J Khulna 2023; 56: 03-07